Entry of Foreign Banks and their Impact on Host Countries - Maria Lehner; Monika Schnitzer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
Foreign bank entry is frequently associated with spillover effects for local banks and increasing competition in the local banking market. We study the impact of these effects on host countries. In particular, we ask how these effects interact and how they depend on the competitive environment of the host banking market. An increasing number of banks is more likely to have positive welfare effects the more competitive the market environment, whereas spillovers are less likely to have positive welfare effects the stronger competition. Hence, competitive effects seem to reinforce each other, while spillovers and competition tend to weaken each other.
Keywords: F37; G21; L13; O16; 330; foreign bank entry; multinational bank; competition in banking; spillover effects